PENGARUH BAURAN PEMASARAN RESTO TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA RUMAH MAKAN RAWON SETAN DI SURABAYA - INDRASWATI, MARIA (Jurnal Pendidikan Tata Niaga (JPTN), 2014)
This study aims to determine the effect of restaurant marketing mix on purchase decisions in the Rawon Setan Restaurant in Surabaya. Where the independent variables are product (X1), price (X2), place (X3), people (X4), and physical evidance (X5) and the dependent variable is the purchase decision (Y). The population in this study are customers of Rawon Setan Restaurant. Samples were taken as 126 respondents by using Purposive Sampling technique with a questionnaire filled out by the consumer. Then the data were analyzed using multiple regression analysis. Then the data were analyzed using multiple regression analysis. This analysis includes Validity Test, Reliability Test, Regression Analysis, Test Classical Assumptions, Hypothesis Testing through Ftest and ttest, and analysis of the coefficient determination (R2) of the coefficient of determination (R²). Based on statistical data analysis, the indicators in this study are valid and reliabel. In the classical assumption test, regression models multikolonieritas free, heterosdastisitas not happen, and the normal distribution. Result of regression, variables showed that Y=1,261+0,292X1–0,339X2+0,942X3+0,464X4+0,431X5. Ftest show simultaneous by product, price, place, people, and physical evidence significantly influence purchasing decisions the value of Ftest at 151,826 significant 0,000. Ttest show is product, price, place, people, and physical evidence partial effect on purchasing decisions purchasing decisions. Figures Adjusted R Square of 0,858 = 86% indicates that purchasing decisions are influenced by the variable product, price, place / location, people (employees), and the physical evidence of 86% while 14% is influenced by other variables not examined. Keywords: Restaurant Marketing Mix, Purchasing Decision